Susceptibility testing of Candida albicans isolated from oropharyngeal mucosa of HIV(+) patients to fluconazole, amphotericin B and Caspofungin. killing kinetics of caspofungin and amphotericin B against fluconazole resistant and susceptible isolates - de Aquino Lemos, Janine (Sociedade Brasileira de Microbiologia, 2009)
A clear understanding of the pharmacodynamic properties of antifungal agents is important for the adequate treatment of fungal infections like candidiasis. For certain antifungal agents, the determination of Minimal Fungicidal Concentration (MFC) and time kill curve could be clinically more relevant than the determination of the Minimal Inhibitory Concentration (MIC). In this study, MIC and MFC to fluconazole, amphotericin B and caspofungin against C. albicans isolates and the killing patterns obtained with caspofungin and amphotericin B against susceptible and resistant strains to fluconazole were determined. The results of MICs showed that all C. albicans isolates were highly susceptible to amphotericin B, but two isolates were fluconazole resistant. The comparative analysis between MIC and MFC showed that MFC of fluconazole was fourfold higher than MIC in 41.9% of the C. albicans isolates. Same values of MFC and MIC of amphotericin B and caspofungin were found for 71% of the isolates. Correlation between time kill curves and MFC of amphotericin B and caspofungin against all 4 isolates tested was observed. The caspofungin killing effect was more evident at MFC in 6 hours of incubation than at MIC in this time, suggesting dependence of concentration. The similarity of results of time-kill curve and MFC values indicate that determination of MFC is an alternative for the detection of the fungicidal activity of these drugs.